Marketing US wrestling 2020 - Parise, A.; O`Neill, S.; Colman, R.; Negri, M.; Sanderson, D.; Williams, S.; Graziano, B.; Legere, M.; Hodgkins, N.; Hicks, J.; O`Brien, C.; Benguche, K.; et al. (2020)
Referencing domestic and global practices, this study provides information on what might be implemented as best practices to advance the product, place, price and promotion of wrestling in the USA. The authors utilized the model of integrated elite and mass sport development from past research which formed the foundation for a questionnaire and interview schedule for US wrestling coaches and administrators to generate a snapshot of perceptions of the current sport system and possibilities for its further development and marketing.